MENINGKATKAN KETERAMPILAN MENGANYAM SARANG KETUPAT MELALUI TEKNIK TOKEN EKONOMI PADA ANAK TUNAGRAHITA RINGAN DI SMPLB PERWARI PADANG - Eri Susanti (Jurnal Penelitian Pendidikan Khusus, 2012)
The research is motivated in learning the skills yet lightweight SMPLB mental retardation children eighth grade that produce handicrafts that have Nili sell crafts kids because there is no viable market when the unit level curriculum  SDLB sixth grade education in the subject of art, culture and skills of the semester II the child should have been able to weave a nest diamond but in fact to date the child is not yet able to weave nests diamond even been given a variety of learning methods, but still lackluster and lazy children in learning. This might be due to the lack of provision of reinforcement from teachers in making reinforcement learning is used has not been able to improve the skills of their web ketupat mild mental retardation in children SMPLB Class VIII. This study aims to improve the skills of their web ketupat mild mental retardation in children through the eighth grade SMPLB Token Economy Technique.Type of research is a class act (classroom action research) is done in the form of collaboration with classroom teachers in four subjects, namely children mild mental retardation SMPLB Perwari SLB class VIII in Padang.